Anti-Inflammatory Activities of Some Plants of Genus Alpinia: Insights from In Vitro, In Vivo, and Human Studies - Yuliawati KM; Febriyanti RM; Sumiwi SA; Levita J (Journal of Experimental Pharmacology)
Kiki Mulkiya Yuliawati,1,2,* Raden Maya Febriyanti,3,* Sri Adi Sumiwi,4,* Jutti Levita4,* 1Doctoral Program in Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Faculty of Mathematics and Natural Sciences, Bandung Islamic University, Bandung, Indonesia; 3Department of Biology Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, Indonesia*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung-Sumedang km 21, Sumedang, 45363, Indonesia, Tel +6222-84288888 Ext 3510, Email jutti.levita@unpad.ac.idAbstract: This narrative review intends to provide thorough information on the anti-inflammatory activities of Alpinia plants, the largest genus of the family Zingiberaceae. The articles were searched on the PubMed database using ‘Alpinia AND anti-inflammatory activity’ as the keywords, filtered to articles published from 2020 to 2024 and free full-text. Of the approximately 248 members of the genus Alpinia plants, the most commonly studied for their anti-inflammatory activities are A. galanga, A. officinarum, A. zerumbet, and A. oxyphylla. Only A. galanga, A. officinarum, and A. zerumbet have been studied in humans. Studies in animal models revealed that the plants contributed as exogenous antioxidants, reduced proinflammatory cytokines, inhibited proinflammatory enzymes, improved gastric acid and gastrointestinal motility, and promoted ulcer healing. The terpenoids, flavonoids (such as kaempferol, quercetin, and galangin), and diarylheptanoids obtained from the rhizomes of these plants may crucially play important roles in their anti-inflammatory activities. These plants did not show toxicity toward numerous normal cell lines (RAW 264.7, IEC-6, HepG2, MT-4, NIH-3T3, Vero cells, human peripheral blood mononuclear cells, and HaCaT) but were toxic to cancer cell lines (HT29). In humans, A. galanga was studied for its effects as psychostimulants improving mental health, improving sperm motility, and erectile dysfunction. Similarly, A. officinarum could improve sperm morphology and idiopathic infertility, whereas A. zerumbet worked as a cardio-myorelaxant in patients with cardiovascular diseases.Keywords: cytokines, flavonoids, interleukins, polyphenols, secondary metabolites, Alpinia genus